An oligonucleotide-functionalized carbon nanotube chemiresistor for sensitive detection of mercury in saliva. Issue 9 (23rd February 2016) - Wordofa, Dawit N.; Ramnani, Pankaj; Tran, Thien-Toan; Mulchandani, Ashok
Abstract : We report a highly selective and sensitive biosensor for detection of both mercuric (Hg 2+ ) and monomethyl mercury (CH3 Hg + ) that are known to be highly toxic to humans. Abstract : Divalent mercuric (Hg 2+ ) ion and monomethyl mercury (CH3 Hg + ) are two forms of mercury that are known to be highly toxic to humans. In this work, we present a highly selective, sensitive and label-free chemiresistive biosensor for the detection of both, Hg 2+ and CH3 Hg + ions using DNA-functionalized single-walled carbon nanotubes (SWNTs). The SWNTs were functionalized with the capture oligonucleotide, polyT, using a linker molecule. The polyT was hybridized with polyA to form a polyT:polyA duplex. Upon exposure to mercury ions, the polyT:polyA duplex dehybridizes and a T–Hg 2+ –T duplex is formed. This structure switch leads to the release of polyA from the SWNT surface and correspondingly a change in the resistance of the chemiresistive biosensor is observed, which is used to quantify the mercury ion concentration. The biosensor showed a wide dynamic range of 0.5 to 100 nM for the detection of CH3 Hg + ions in buffer solution with a sensitivity of 28.34% per log (nM) of CH3 Hg + . Finally, real world application of the biosensor was demonstrated by the detection of Hg 2+ and CH3 Hg + ions in simulated saliva samples spiked with a known concentration of mercury ions.